Phylogenetic composition and structure of tree communities shed light on historical processes influencing tropical rainforest diversity. Issue 4 (8th April 2016) - Carlucci, Marcos B.; Seger, Guilherme D. S.; Sheil, Douglas; Amaral, Iêda L.; Chuyong, George B.; Ferreira, Leandro V.; Galatti, Ulisses; Hurtado, Johanna; Kenfack, David; Leal, Darley C.; Lewis, Simon L.; Lovett, Jon C.; et al.
Abstract : The Neotropics, Afrotropics and Madagascar have different histories which have influenced their respective patterns of diversity. Based on current knowledge of these histories, we developed the following predictions about the phylogenetic structure and composition of rainforest tree communities: (Hypothesis 1) isolation of Gondwanan biotas generated differences in phylogenetic composition among biogeographical regions; (H2) major Cenozoic extinction events led to lack of phylogenetic structure in Afrotropical and Malagasy communities; (H3) greater angiosperm diversification in the Neotropics led to greater phylogenetic clustering there than elsewhere; (H4) phylogenetic overdispersion is expected near the Andes due to the co‐occurrence of magnoliids tracking conserved habitat preferences and recently diversified eudicot lineages. Using abundance data of tropical rainforest tree species from 94 communities in the Neotropics, Afrotropics and Madagascar, we computed net relatedness index (NRI) to assess local phylogenetic structure, i.e. phylogenetic clustering vs . overdispersion relative to regional species pools, and principal coordinates of phylogenetic structure (PCPS) to assess variation in phylogenetic composition across communities. We observed significant differences in phylogenetic composition among biogeographical regions (agreement with H1). Overall phylogenetic structure did not differ among biogeographical regions, but results indicated variation from Andes to Amazon. We found widespread phylogenetic randomness in most Afrotropical and all Malagasy communities (agreement with H2). Most of central Amazonian communities were phylogenetically random, although some communities presented phylogenetic clustering (partial agreement with H3). We observed phylogenetic overdispersion near the Andes (agreement with H4). We were able to identify how differences in lineage composition are related to local phylogenetic co‐occurrences across biogeographical regions that have been undergoing different climatic and orographic histories during the past 100 Myr. We observed imprints of the history following Gondwana breakup on phylobetadiversity and local phylogenetic structure of rainforest tree communities in the Neotropics, Afrotropics and Madagascar.